Peningkatan Hasil Belajar Tematik Terpadu Menggunakan Model Contextual Teaching and Learning (CTL) di Kelas IV SDN 17 Pakan Kurai Bukittinggi - Ihsan, Fajri; Zuryanty, Zuryanty (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2019)
This study aims to describe the improvement of Integrated Thematic learning outcomes using the CTL (Contextual Teaching Learning) Model in class IV SDN 17 Pakan Kurai Bukittinggi academic year 2018/2019. This type of research is classroom action research with qualitative and quantitative approaches. The research subjects were teachers and 32 fourth grade students of SDN 17 Pakan Kurai. The study was conducted in two cycles, cycle I two meetings and cycle II one meeting. This is evidenced by the results of cycle 1 research aspects of the assessment of RPP cycle I 83.55% (B) increased in cycle II to 90% (AB) an increase of 6.45 %%, aspects of the implementation of the first cycle teacher 77.5% (B) increased in cycle II to 90% (AB) an increase of 12.5%, aspects of the action of students in the first cycle 78.5% (B) increased in the second cycle to 85% an increase of 6.5%, and the learning outcomes of the first cycle with average -72 (B) and cycle II increased to 91.5 (A) an increase of 19.5.